Attenuating diagonal decoupling with robustness for velocity-varying 4WS vehicles. (November 2016) - Li, Mingxing; Jia, Yingmin; Matsuno, Fumitoshi
Abstract: A control strategy with four controllers is presented to overcome the dilemma of enhancing the robustness or decoupling for four-wheel-steering (4WS) vehicles with uncertainties and disturbances. Influences of steering system, uncertainties and disturbances on the traction system are attenuated by the first controller such that traction and steering systems are controlled separately. Robustness of the steering system is ensured by the second controller. Attenuating diagonal decoupling (ADD) is established by the remaining two controllers: coupling caused by uncertainties is rejected and diagonal decoupling is obtained. Simulations show that decoupling with better robustness is obtained. Abstract : Highlights: The combined issue of decoupling and robust control 3DOF 4WS vehicles is solved. Attenuating diagonal decoupling is used to solve the issue of the uncertain system. Decoupling and robust performances are ensured for velocity-varying 4WS vehicles. The handling stability and steerability are improved simultaneously.